Non Transmissible Chronic Diseases: Current Magnitude and Future Trends - Miguel Ángel Serra Valdés; Melissa Serra Ruíz; Marleny Viera García (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
The treatment to non-transmissible chronic diseases is currently on of the greatest challenges faced by the health systems worldwide. This is due to the fact that these diseases affect all age groups, all regions and countries regardless their level of development. Cuba is not the exception. The World Health Organization, however, points out that there is an inadequate management of these ailments, for different reasons, in most of the health systems. The objective of this article is the awareness of the current and future problem of chronic diseases where health promotion and prevention still is the main weapon to fight the challenge. The importance of these elements should be taken into consideration from the personnel in training, the need to set present and future strategies to guarantee the health of our population, mainly from the primary health care attention and organizations linked to them. The most affected population should be aware of what suffering from a chronic disease represents in general.